2019
DOI: 10.1308/rcsann.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on outcomes of salvage therapy in patients with tumour recurrence during ‘watch and wait’ in rectal cancer

Abstract: Introduction The ‘watch and wait’ approach has recently emerged as an alternative approach for managing patients with complete clinical response in rectal cancer. However, less is understood whether the intervention is associated with a favourable outcome among patients who require salvage therapy following local recurrence. Materials and methods A comprehensive systematic search was performed using EMBASE, PubMed, MEDLINE, Journals@Ovid as well as hand searches; published between 2004 and 2018, to identify st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In the OnCoRe project[ 104 ], 88% of patients with non-metastatic local regrowths were salvaged, a slightly higher rate than reported by Kong et al[ 162 ] (83.8%) and Smith et al[ 163 ] (85%), and well above the 68.4% rate described by On et al[ 164 ] and the 69% rate reported in the International Watch and Wait Database[ 107 ]. Moreover, the salvage rate in the OnCoRe study were close to those described by Chadi et al[ 165 ] (89%) and by the Habr-Gama group (90%)[ 161 ] (Table 2 ).…”
Section: Outcomes and Management Of Tumour Regrowthmentioning
confidence: 89%
See 1 more Smart Citation
“…In the OnCoRe project[ 104 ], 88% of patients with non-metastatic local regrowths were salvaged, a slightly higher rate than reported by Kong et al[ 162 ] (83.8%) and Smith et al[ 163 ] (85%), and well above the 68.4% rate described by On et al[ 164 ] and the 69% rate reported in the International Watch and Wait Database[ 107 ]. Moreover, the salvage rate in the OnCoRe study were close to those described by Chadi et al[ 165 ] (89%) and by the Habr-Gama group (90%)[ 161 ] (Table 2 ).…”
Section: Outcomes and Management Of Tumour Regrowthmentioning
confidence: 89%
“…In the longer term, the Habr-Gama group reported a 5-year OS of 63.3% in patients who underwent salvage surgery[ 166 ], substantially less than the 85% reported in the International Watch and Wait Database[ 107 ]. On et al[ 164 ] found no significant differences in survival rates between salvage and upfront surgery (92.3% vs 92.9%, respectively) (Table 2 ).…”
Section: Outcomes and Management Of Tumour Regrowthmentioning
confidence: 94%
“…Considerable information is available on the risk of distant metastases, intraluminal regrowth and subsequent surgical salvage [52]. In this meta-analysis, the relative risk of overall mortality in the salvage therapy group was 2.42 (95% CI 0.96-6.13) compared with the group who had conventional surgery, but this was not statistically significant (p > 0.05).…”
Section: Reviewmentioning
confidence: 70%
“…Other small institutional retrospective studies [46,47], propensity score-matched cohort analyses [48] and modest population databases (less than 5000 patients [49] support the strategy). There have been several meta-analyses [50][51][52]. We identified few prospective [17] and no relevant randomized trials.…”
mentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have concluded that although the local recurrence rate of the watch-and-wait group could be higher than in the TME group when promptly treated by salvage therapy, the watch-and-wait strategy could achieve similar oncologic outcomes as the TME approach. Salvage surgery (APR, LAR, TaTME) is possible in 83.8% of patients who develop a tumor regrowth with the “watch-and-wait” approach with no difference in overall survival and disease-free survival between patients who received immediate surgery without differences in relative risk of overall mortality and relative risk of disease-specific mortality [ 122 , 171 , 172 ].…”
Section: Debated Issuesmentioning
confidence: 99%